Assembly line Optimization: A systematic review of various algorithms, applications & drawbacks - Gurav, Vijay; Badgujar, Abhishek; Dhage, Aditya (AGUSPATI Research Institute, 2025)
One of the most popular production methods is assembly line manufacturing. The assembly line balance problem, which is used to quickly build large quantities of a consistent product, is focused on decreasing the number of workstations, lowering cycle time, maximizing work cohesion, and maximizing workload uniformity. The initial purpose of assembly lines was to produce standardized goods in large quantities at a reasonable cost. A production unit's assembly line consists of a number of employees and equipment. An assembly line is used to produce the components in a production unit. During processing, the product travels along this line. In a flexible manufacturing system, assembly lines have changed throughout time from straight lines with a single model to mixed lines with numerous models, U-shaped lines, and lines with parallel workstations. Reducing the number of work stations and balancing the assembly line based on the intended production volume each shift are the primary goals of system assembly line planning. Various assembly line balance difficulties (ALB) have been examined and described in this paper. Researchers can greatly benefit from the creation of a mathematical model to address the assembly line balancing and sequencing difficulties.